Osmanlı Çini Sanatında Bahar Dalı Kompozisyonları (16.-17. Yüzyıl). - Çakır, Dilek; Uysal, Zekiye (Electronic Turkish Studies)
In the history of Ottoman culture, the 16th and 17th centuries are the periods in which various changes were experienced in terms of decorative arts. The flowers depicted in the naturalistic style by Karamemi in particular, the chief nakkash of the Ottoman Palace during the reign of Kanuni Sultan Süleyman the Magnificent, brought about a significant difference in the floral decorations.In addition to the motifs such as tulips, carnations, roses, hyacinths and irises, which are garden flowers, which is one of the important motifs of the naturalist style, is the fruit tree in spring, or the motif, which is also called springtime tree or spring branches according to its composition, in many handicrafts, especially in the art of tiles. The subject of our study is the spring branch compositions on the tiles, which are seen on the Ottoman buildings and dated to the mentioned centuries.The motifs were processed in various sizes and arrangements on the wall tiles, and the compositions were used both inside and outside the mosques, palaces, tombs, pavilions, baths and libraries.Tiles are located on the panels on the walls of the buildings, in the niches and corners of the altars, in the pulpit kiosk, on the corners of the panels and windows, and on the window and door pediments.However, it is noteworthy that the spring branch compositions on the tiles are not evaluated by considering them as a whole.In the study, 29 structures in which the spring branch motif is seen in the tile decorations of these periods were examined, and 52 examples with different compositions of the motif were determined.In some buildings, there are identical panels with the same composition.Our aim is to determine and evaluate the design features and composition diversity of the spring branch motif, which we generally classify as tree and branch.